1997
DOI: 10.1089/gte.1997.1.99
|View full text |Cite
|
Sign up to set email alerts
|

The 22q11.2 Deletion: Screening, Diagnostic Workup, and Outcome of Results; Report on 181 Patients

Abstract: A submicroscopic deletion of chromosome 22q11.2 has been identified in the majority of patients with the DiGeorge syndrome, velocardiofacial syndrome, conotruncal anomaly face syndrome, and in some patients with isolated conotruncal cardiac anomalies, Opitz G/BBB syndrome, and Cayler cardiofacial syndrome. We have evaluated 181 patients with this deletion. We describe our cohort of patients, how they presented, and what has been learned by having the same subspecialists evaluate all of the children. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
2
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 44 publications
2
109
2
9
Order By: Relevance
“…This was not done in our study. McDonald-McGinn et al reported hypocalcemia in 77 of 158 (49%) patients with a confirmed del(22)(q11) (14). In a large European cohort, 60% of patients were hypocalcemic (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not done in our study. McDonald-McGinn et al reported hypocalcemia in 77 of 158 (49%) patients with a confirmed del(22)(q11) (14). In a large European cohort, 60% of patients were hypocalcemic (6).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of hypoparathyroidism may be precipitated during periods of increased metabolic demand such as cardiopulmonary bypass (18). The del(22)(q11) typically occurs de novo, although it is inherited in about 10-20% of cases with a marked excess of maternally inherited deletions (14). Even within one kindred family, the phenotypic variability including that of parathyroid gland dysfunction, may be as marked as between unrelated individuals (8).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Cognitive deficits are seen in the majority (80-100%) of individuals with 22q11DS 3 with impairments in sustained attention, executive function, memory, visual-spatial perception, [4][5][6] along with anxiety disorders, attention deficit disorder and poor social skills (40-50%). [7][8][9] A uniquely elevated risk of schizophrenia spectrum disorders (25%), bipolar disorder (B5%) and major depression (B10%) occurs in adolescence and young adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…DiGeorge syndrome, 1,2 velocardiofacial syndrome (VCFS), 3 and conotruncal anomaly face syndromes, 4 and some patients with autosomal dominant Opitz G/BBB syndrome, 5,6 isolated conotruncal cardiac anomalies, 7 and Cayler cardiofacial syndrome 8 have been associated with the 22q11.2 deletion. The pattern of physical findings associated with the 22q11.2 deletion varies from patient to patient 9 and includes a conotruncal cardiac defect, palatal anomalies such as an overt cleft palate or velopharyngeal incompetence, thymic aplasia, or hypoplasia, T-cell abnormalities, and minor facial anomalies. These signs are now widely recognized.…”
mentioning
confidence: 99%